2017
DOI: 10.1597/15-341
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Safety of Iliac Bone Harvest Using an Acumed Drill: A Simulated Radiographic Study of 100 Patients

Abstract: Acumed assisted iliac crest bone graft harvest is a safe technique in which substantial amount of cancellous bone can be obtained. The low risk of bowel perforation can be further minimized by limiting the depth of drill bit penetration to less than 3 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…They postulated that limiting the trephine depth to 3 cm reduces the risk of visceral injury based on their CT findings. 8 Caminiti et al corroborate these results, stating an increased risk of fracture to the inner or outer table with trephine depth more than 30 mm. 7 Missiuna et al describe the use of a Steinman pin as a trochar inserted into the iliac crest, over which they guided the circular trephine during bone graft harvest.…”
Section: Volume and Type Of Harvested Bonementioning
confidence: 80%
See 2 more Smart Citations
“…They postulated that limiting the trephine depth to 3 cm reduces the risk of visceral injury based on their CT findings. 8 Caminiti et al corroborate these results, stating an increased risk of fracture to the inner or outer table with trephine depth more than 30 mm. 7 Missiuna et al describe the use of a Steinman pin as a trochar inserted into the iliac crest, over which they guided the circular trephine during bone graft harvest.…”
Section: Volume and Type Of Harvested Bonementioning
confidence: 80%
“…25 Stranix et al assessed the potential volume of cancellous bone graft harvest based on CT measurements. 8 The maximum cancellous volume they projected that could be safely harvested increased with age, with 12 cc in 8-year-olds, to 17 cc in 12-year-olds, using a 42 mm drill bit. 8 Despite these predictions, such harvest yields were not corroborated in clinical studies.…”
Section: Volume and Type Of Harvested Bonementioning
confidence: 99%
See 1 more Smart Citation
“…Six papers studied simulation 37-42 , with the different types summarized effectively by Vanikipuram et al 42 . These studies showed that simulation can successfully be used to reduce plunging depth in trainee surgeons 38,39 and that computer-based simulation was found to provide effective and transferable skills for inexperienced surgeons 40,41 .…”
Section: Resultsmentioning
confidence: 99%
“…& N.P.). Cancelous bone graft was harvested from either iliac crest, however dissection was minimized via use of the 7 mm Acumed reamer system (Acumed, Hillsboro, OR) 5,6 and prior to wound closure all patients received local infiltration of liposomal bupivacaine. Following bone graft harvest, the recipient site was prepared, the bone graft placed, and the wound closed in the usual fashion.…”
Section: Methodsmentioning
confidence: 99%